Growth Performance And Genetic Variation Of Four Acacia Species Planted In Pahang, Malaysia - Mahat, Mohd Noor (2007)

(untitled)
Acacia mangium Willd, Acacia auriculiformis A. Cunn. ex Benth., Acacia crassicarpa A. Cunn. ex Benth. and Acacia aulacocarpa A. Cunn. ex Benth. are the four fast-growing tropical acacias which have received high priority for genetic assessment and improvement in the Asian region. Despite their rapid early growth and tolerance to a wide range of environmental conditions, only A. mangium has been widely planted in the Compensatory Forest Plantation Programme in Malaysia. The seed sources utilised in the plantation were however, unselected and originated from a narrow genetic base. Therefore, this study was conducted at Kampung Aur Gading, Kuala Lipis, Pahang to evaluate the genetic variation and growth performance of a base breeding populations of Acacia species in terms of their quantitative and qualitative growth characteristics. Estimates of some parameters such as genetic correlation and heritability were also made. Twenty progenies each of the species were collected from two geographic regions namely Queensland and Papua New Guinea were used in this study. This trial was laid out in a randomized complete block design with four replications.Generally all species adapted and performed well in local condition and their growth performances were significantly different (P< 0.05) between species, provenance and family. A. mangium was the best performer in almost all of the traits tested, followed by A. crassicarpa, A. auriculiformis and A. aulacocarpa. Concurrently, all species exhibited high intra species variation for all the traits assessed. There were also significant genetic variation between regions, between provenances within region and between families within the provenances exists in the quantitative traits assessed for all species. The populations collected from Papua New Guinea, generally, outperformed those from Queensland in quantitative growth traits except for stem quality which appeared otherwise. The progenies in the family also exhibit high genetic variability with variance component ranging from 39% to 93.7% of the total variance. Out of these, few individuals were found to be exceptionally good performer, even from the poor families such as JSL3777 of A, mangium, MHL14 of A. crassicarpa, BH14068 of A. auriculiformis and GB100 of A. aulacocarpa. Among the top performing families were KN097, CG1853 and JSL380 of A. mangium, BVG2609 and MHL13A of A. crassicarpa, GB098, MM1016 and AR10 of A. aulacocarpa and BH14607 and JSL363 of A. auriculiformis. There were significant differences between species (at P<0.05) for selected wood properties tested. A. aulacocarpa gave the highest wood density of 0.59 g/cm3, followed by A. auriculiformis (0.54 g/cm3), Acacia crassicarpa (0.51 g/cm3) and A. mangium (0.43 g/cm3). On the contrary, the order of ranking differed in fiber length where, A. crassicarpa produced the longest fiber length (0.91mm), followed by A. mangium (0.85mm), A. aulacocarpa (0.83mm) and A. auriculiformis (0.83mm).The study found that all species were efficient in their photosynthetic capabilities since they produced Fv/Fm values above 0.80 and were not significantly different. Generally the heritability estimates were variable between traits and between species. The heritability estimates of quantitative growth traits for A. aulacocarpa were found to be almost consistent for all traits ranging from 0.36 to 0.40. Similarly, A. mangium gave estimates ranging from 0.30 to 0.36. On the contrary A. auriculiformis gave comparatively more variable estimates ranging from 0.23 to 0.37. A. crassicarpa recorded comparatively lower estimates ranging from 0.20 to 0.30. The heritability estimates for the qualitative traits were however, low with majority of them estimating narrow sense heritabilities below 0.20. The heritability estimates for wood properties and chlorophyll fluorescence varied significantly from none (0.0) to moderate (0.32) for families of all species tested.The phenotypic and genetic correlations varied widely ranging from 0.0 to 0.96 for the former and from 0.0 to 0.83 for the latter, respectively. Generally, these correlations were found to vary between traits as well as between species. The correlations between growth traits and stem qualitative traits were generally moderate (0.4 –0.6) to high (above 0.6). The correlations between quantitative traits and other traits were found to be generally low (below 0.4) whereas correlations between physiological traits and wood properties and with other traits were generally very low (below 0.1) or even not correlated at all. This study indicated that further improvement could still be done on this base breeding population by employing further selection on a few selected traits at a time for the development of advanced breeding or even for the production populations.